2019
DOI: 10.1213/ane.0000000000004393
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Neuromuscular Blocking Drug Use and Ventilation Technique on Complications in the Pediatric Difficult Intubation Registry Using Propensity Score Matching

Abstract: BACKGROUND: Ventilation is critical in airway management, and failure can be fatal. The optimal ventilation approach for endotracheal intubation in children with difficult airways remains controversial. The Pediatric Difficult Intubation (PeDI) Registry is an international multicenter registry that collects intubation data in difficult to intubate children. The registry captures the initial (at induction) and final ventilation technique (at intubation), the use of neuromuscular blocking drugs (NMBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Nevertheless, the results of the present study are more informative than those reported by the registries that are voluntary based and are subject to underreporting. 5,29 The second limitation is attributable to the nature of the study itself as information was gathered from 165 centres that were willing to participate, and thus, a selection bias may be perceived as most centres are specialised and the overall incidence of difficult intubation could be underestimated for non-participating or non-dedicated paediatric centres. 6,9 The (non-)availability of videolaryngoscopes or fibreoptic endoscopes in the participating centres may also have affected the final results.…”
Section: Risk Factormentioning
confidence: 99%
“…Nevertheless, the results of the present study are more informative than those reported by the registries that are voluntary based and are subject to underreporting. 5,29 The second limitation is attributable to the nature of the study itself as information was gathered from 165 centres that were willing to participate, and thus, a selection bias may be perceived as most centres are specialised and the overall incidence of difficult intubation could be underestimated for non-participating or non-dedicated paediatric centres. 6,9 The (non-)availability of videolaryngoscopes or fibreoptic endoscopes in the participating centres may also have affected the final results.…”
Section: Risk Factormentioning
confidence: 99%
“…Neuromuscular blockade agents have traditionally been avoided in patients with difficult airways. An observational study from the aforementioned Pedi Registry found an association between spontaneous ventilation technique (versus controlled ventilation with or without neuromuscular blockade) and increased nonsevere complications . Light anesthesia was the likely cause of these complications as patients in the spontaneous group had more reported airway reactivity.…”
Section: Airway Management In the Operating Roommentioning
confidence: 99%
“…A randomized controlled trial of 160 adult patients with anticipated difficult airways demonstrated the use of this combined technique of VL with a flexible scope as stylet resulted in higher first‐pass success rates, shorter time to successful intubation, and lower rates of airway injury when compared with hyperangulated VL alone . This technique has also been used successfully in children who are difficult to intubate . It provides improved maneuverability and visualization over either technique alone; however, it does require multiple practitioners to operate the two devices and likely performs better in situations of anticipated difficulty rather than as a rescue technique.…”
Section: Combined Techniquesmentioning
confidence: 99%
“…The ETT is connected to the anesthesia circuit, again reconfirming oxygenation and ventilation (Figure A). Following successful SGA placement, the provider may maintain spontaneous ventilation or choose to control ventilation with or without the use of neuromuscular blocking drugs as dictated by the clinical situation . A triple port, swivel adapter is connected to the ETT, which, in turn, is connected to the anesthesia circuit to allow oxygenation and ventilation throughout the period of flexible laryngotracheobronchoscopy.…”
Section: Combined Techniquesmentioning
confidence: 99%